Aspects of thermal radiation for the second law analysis of magnetized Darcy–Forchheimer movement of Maxwell nanomaterials with Arrhenius energy effects - Khan, Umair; Khashi’ie, Najiyah Safwa; Vinodkumar Reddy, Mulinti; Malleswari, Kakanuti; Ajithkumar, Moorthi; Elkamchouchi, Dalia H.; Ali, Farhan; Nath, Jintu Mani (Walter de Gruyter GmbH, 2025)
The present mathematical model investigates convective heat transfer in the Darcy–Forchheimer flow of a magnetoMaxwell nanofluid over a porous stretched sheet. The impacts of convective boundary conditions, activation energy, Joule heating, thermal radiation, and energy production are also considered in the flow model. Additionally, the heat transmission process is described using the Cattaneo–Christov heat flow model. A system of highly non-linear ordinary differential equations is built using suitable similarity transformations. The model has been numerically tackled utilizing MALAB’s bvp4c package. Computational findings are calculated for liquid velocity, liquid temperature, nanoparticle concentration, and total entropy creation as functions of transverse displacement for investigating the velocity, mass, and thermal properties of the Maxwell nanoliquid under suitable assumptions and boundary conditions. Oscillations in friction factor, mass, and heat transfer rates have also been examined. It is observed that the velocity distribution improves as the thermal and concentration Grashof numbers increase, whereas it decreases as the suction parameter and Darcy–Forchheimer parameter increase. It is further reported that the concentration upsurges with larger estimates of activation energy in the central component of the geometry. This research has practical applications in escalating thermal transfer systems employed in industrial procedures, freezing technologies, and energy systems. It supports heightening thermal management in reactors, geothermal structures, and polymer processing.